Containment and support: similarities and variation in Lithuanian, Latvian and Estonian - Žilinskaitė-Šinkūnienė, Eglė; Šķilters, Jurģis; Zariņa, Līga; Bērziņa, Nora (Baltistica, 2019)
This paper aims to describe how spatial semantic categories of containment and support are expressed in three languages, – Lithuanian, Latvian and Estonian, – which are spoken in the same area, though only the first two of them are genealogically related. Our research is based on a production task (n = 60 for each language) consisting of answers to picture stimuli representing major subtypes of containment and support: full containment, partial containment and interlocking for containment and support-from-below, adhesion, hanging and encirclement with contact for support. The results show that the core types of containment and support, namely, full-containment and support-from-below, are expressed most homogenously and using least terms in all three languages, but other sub-types trigger more variety. Cross-linguistically, containment is expressed similarly in the Baltic languages, but in terms of conceptualization and expression of support, Latvian and Estonian share more commonalities. This provides new evidence for semantic diversity of the Baltic languages and language-contact induced peculiarities of Latvian.